Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1371/journal.pone.0122094
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Numerical Model of Cell Morphology during Migration in Multi-Signaling Substrates

Abstract: Cell Migration associated with cell shape changes are of central importance in many biological processes ranging from morphogenesis to metastatic cancer cells. Cell movement is a result of cyclic changes of cell morphology due to effective forces on cell body, leading to periodic fluctuations of the cell length and cell membrane area. It is well-known that the cell can be guided by different effective stimuli such as mechanotaxis, thermotaxis, chemotaxis and/or electrotaxis. Regulation of intracellular mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 107 publications
0
26
0
Order By: Relevance
“…Despite the frequency with which they have and continue to be utilized for migration studies, 2D models have significant limitations, primarily owing to the fact that migration in vivo typically occurs in a 3D space. More recent work has shown that topography and dimensionality, among other parameters [25,39], play a critical role in determining migratory phenotype and the mechanical responses of cells. Micromolded and micromachined 2D surfaces [40] as well as tunably compliant 2D substrates such as polyacrylamide (PA) [39,41] or collagen gels [42][43][44] partially resolve the limitations of 2D systems by allowing for tuning of topography and stiffness, but still do not entirely account for dimensional cues from the environment.…”
Section: Two-dimensional Versus 3d Models and Methods To Studymentioning
confidence: 99%
“…Despite the frequency with which they have and continue to be utilized for migration studies, 2D models have significant limitations, primarily owing to the fact that migration in vivo typically occurs in a 3D space. More recent work has shown that topography and dimensionality, among other parameters [25,39], play a critical role in determining migratory phenotype and the mechanical responses of cells. Micromolded and micromachined 2D surfaces [40] as well as tunably compliant 2D substrates such as polyacrylamide (PA) [39,41] or collagen gels [42][43][44] partially resolve the limitations of 2D systems by allowing for tuning of topography and stiffness, but still do not entirely account for dimensional cues from the environment.…”
Section: Two-dimensional Versus 3d Models and Methods To Studymentioning
confidence: 99%
“…This force drives the cell body forward and is directly proportional to the cell stress, σ cell . Representing the cell by a connected group of finite elements, the nodal traction force of the cell can be represented as [ 24 , 25 ] where e i denotes a unit vector passing through the i th node of the cell membrane towards the cell centroid ( Fig 1-a ). S represents the cell membrane area and ζ is a dimensionless parameter named “adhesivity” which is directly proportional to the concentration of the ligands at the leading edge of the cell, ψ , the total number of available receptors, n r , and the binding constant of the cell integrins, k .…”
Section: Model Formulationmentioning
confidence: 99%
“…To migrate, cells extend local protrusions by exerting a protrusion force to evaluate their surrounding substrate. This refers to the actin polymerization and differs from the cytoskeletal contractile force transmitted to the substrate [ 22 , 25 , 31 ]. It is a random force that causes cells to move along a directed random path towards the effective cue.…”
Section: Model Formulationmentioning
confidence: 99%
“…Thus, we performed TF microscopy on cells plated onto a fluorescent bead-impregnated gel substrate as describedp r e v i o u s l y( 2 9 ) .W et h e n compared net and total TF magnitudes and their localization. Based on both experimental and computational definitions used by others, we define net TF magnitude as the magnitude of the sum of cellular TF vectors and total TF magnitude as the sum of the magnitudes of cellular TF vectors (4,40,41).…”
Section: Generation Of Tfs In Colxvii Kd Keratinocytesmentioning
confidence: 99%